(untitled) (Journal of Sciences & Technology, 2018)
The north-east area of Constantine has a very complex geological setting. The variety of sedimentary rocks such as sandstone and clay in abundance, represent a big importance in the industry and road infrastructure. The X-ray diffraction (XRD) analysis, Scanning Electron Microscopy SEM/EDS, FTIR spectroscopy of sandstone and clay are required for qualitative and quantitative analysis of the existing phases. In addition, chemical analysis of the same samples is required to confirm the XRD, EDS (Energy Dispersive X ray Spectroscopy) and FTIR spectroscopy results. The results of this multidisciplinary study, obtained by various analytical techniques, show a good agreement on the existing phases.